An International Collaborative Study to Investigate Standardisation of Hirudin Potency - Longstaff, Colin; Wong, Man-Yu; Gaffney, Patrick J (Thrombosis and Haemostasis, 1993)
An international collaborative study has been carried out to investigate the reproducibility of hirudin assays in 13 laboratories using four recombinant hirudins and one natural, sulphated product. A simple assay procedure was proposed involving the titration of α-thrombin with inhibitor and measurement of residual activity using a chromogenic substrate. A standard α-thrombin preparation was supplied to ensure that this reagent was of uniform quality throughout the study. The method appeared to present no difficulties and laboratories reported similar potencies for the 5 hirudin samples, in line with expected values. This gave 200–222 Thrombin Inhibitory Units/ampoule (TIU/ampoule) of lyophilised hirudin, with geometric coefficient of variation (gcv) values ranging from 10.15–15.97%. This corresponds to specific activities of approximately 14,300–15,900 TIU/mg protein. This is close to the upper limit of previously reported values of specific activity. We conclude that the precision of this determination compared with the wider range of values in the literature (8,000–16,000 thrombin inhibitory units [TIU]/mg) results from the use of good quality standard α-thrombin by all laboratories. This study has important implications for hirudin standardisation.